Cloning and sequence characterization of lactoferrin gene of Indian riverine buffalo - KUMARI, N; GOYAL, S; DUBEY, P K; SINGH, S; NIRANJAN, S K; GUPTA, N; PRASAD, A; KATARIA, R S (The Indian Journal of Animal Sciences, 2014)
Lactoferrin (Lf) is a component of the natural protection system of animals. The present study was undertaken to characterize the buffalo lactoferrin gene by cloning and sequence analysis. Total RNA was isolated from the lactating buffalo mammary gland tissue and lactoferrin cDNA was synthesized by RT-PCR technique, then cloned and sequenced. Sequence obtained from the cloned product was analyzed and submitted to NCBI GenBank (Acc. No. JF825526). The buffalo Lf sequence revealed a 2127 nucleotide long ORF coding for 708 amino acids with a signal peptide of 19 amino acids. Comparison with other livestock species revealed buffalo lactoferrin having 71– 97% homology at nucleotide level and 64–96% homology at amino acid level highest with cattle as compared to other species. Based on Lf c-DNA sequences, the phylogenetic analysis also indicated that buffalo Lf having a close relationship with that of cattle. The 3D structure of buffalo lactoferrin was generated by Swiss-model and it was verified by PDBsum, PROCHEK, ProSA z-score and ProQ, which was proved to be satisfactory. Preliminary information generated will be helpful in utilizing this important molecule for further studies in buffalo.